2013
DOI: 10.1002/jbm.a.34903
|View full text |Cite
|
Sign up to set email alerts
|

New sol‐gel bioactive glass and titania composites with enhanced physico‐chemical and biological properties

Abstract: We developed TiO2 matrix composites modified by sol-gel bioactive glasses (SBG) of either high CaO content (A2) or high SiO2 content (S2). The latter were mixed with titanium dioxide (TiO2) at 75:25, 50:50, and 25:75 weight ratios and sintered at 1250°C for 2 h. We examined the effects of various types (A2 or S2) and compositional TiO2 :SBG ratios on the mechanical properties of resulting composites, their bioactivity and human bone marrow mesenchymal stem cells (MSC) response. The chemistry of SBGs influenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…It was also shown that glass composition plays a key role in affecting the biological properties of HA‐, polymer (PLGA, PCL)‐ and TiO 2 ‐based composites, in which sol‐gel bioactive glass have been incorporated. The research group led by Cholewa‐Kowalska extensively investigated the effect of different amounts of SiO 2 in the glass on the biological properties of the composites and found that, except for HA‐based materials, where cell viability and ALP cellular activity were improved with respect to pure HA regardless of silica content, lower SiO 2 amounts induced, in all other cases, an enhanced differentiation of bone marrow precursor cells into an osteoclastic phenotype and a reduction in osteoblast‐like cell metabolism. Moreover, it was demonstrated that a meaningful relationship between ALP activity, glass chemical composition and processing of scaffolds exists…”
Section: Other Forms Of Applications: Coatings Fibres and Compositesmentioning
confidence: 99%
“…It was also shown that glass composition plays a key role in affecting the biological properties of HA‐, polymer (PLGA, PCL)‐ and TiO 2 ‐based composites, in which sol‐gel bioactive glass have been incorporated. The research group led by Cholewa‐Kowalska extensively investigated the effect of different amounts of SiO 2 in the glass on the biological properties of the composites and found that, except for HA‐based materials, where cell viability and ALP cellular activity were improved with respect to pure HA regardless of silica content, lower SiO 2 amounts induced, in all other cases, an enhanced differentiation of bone marrow precursor cells into an osteoclastic phenotype and a reduction in osteoblast‐like cell metabolism. Moreover, it was demonstrated that a meaningful relationship between ALP activity, glass chemical composition and processing of scaffolds exists…”
Section: Other Forms Of Applications: Coatings Fibres and Compositesmentioning
confidence: 99%
“…Other ceramics utilized for bone tissue engineering include bioactive glasses, glass-ceramics, silica and titania. [8][9][10][11][12] Both synthetic and natural polymers have been investigated as bone scaffold materials. Synthetic polymers of interest include polyesters such as polycaprolactone (PCL), 13,14 poly(lactic acid) (PLA), poly(glycolic acid) (PGA) and poly(latic-co-glycolic acid) (PLGA).…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21] Compared to the conventional melting method, sol-gel derived SBG presented a uniform chemical structure and high bioactivity in vitro and in vivo. [22][23][24][25][26] To optimize the properties for bone regeneration, using bioactive agents, sol-gel derived SBG microscale and nanoscale particles have been utilized to prepare polymer composites. [27][28][29] To further improve the chemical structure and tailor the properties of composites, a softened bioactive glass sol, with a molecular-level composition, has been previously reported to fabricate bioactive inorganic-polymer hybrid biomaterials.…”
Section: Introductionmentioning
confidence: 99%